2015
DOI: 10.1111/mec.13124
|View full text |Cite
|
Sign up to set email alerts
|

Are extra‐pair males different from cuckolded males? A case study and a meta‐analytic examination

Abstract: Traditional models for female extra-pair matings assume that females benefit indirectly from extra-pair mating behaviour. Under these so-called adaptive models, extra-pair males are hypothesized to have more compatible genotypes, larger body size, exaggerated ornaments or to be older than cuckolded males. Alternatively, ('nonadaptive') models that consider female extra-pair matings to be a by-product posit that female extra-pair mating can be maintained even if there is no benefit to females. This could happen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 87 publications
4
131
3
1
Order By: Relevance
“…Thus, the female paired with such a male may gain EPOs while, simultaneously, the male may not provide a high level of paternal care. Extrapair sires are predominantly older males (Wetton et al 1991;Cleasby and Nakagawa 2012;Hsu et al 2015), which could mean that correlated differences in parental investment between males with and without EPP could indirectly be driven by male age. Several studies have shown that older males are better at obtaining EPPs and also invest more into paternal care than younger males (Kempenaers and Sheldon 1997;Houston and McNamara 2002;Velando et al 2006;Hammers et al 2012).…”
Section: The Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the female paired with such a male may gain EPOs while, simultaneously, the male may not provide a high level of paternal care. Extrapair sires are predominantly older males (Wetton et al 1991;Cleasby and Nakagawa 2012;Hsu et al 2015), which could mean that correlated differences in parental investment between males with and without EPP could indirectly be driven by male age. Several studies have shown that older males are better at obtaining EPPs and also invest more into paternal care than younger males (Kempenaers and Sheldon 1997;Houston and McNamara 2002;Velando et al 2006;Hammers et al 2012).…”
Section: The Problemmentioning
confidence: 99%
“…We sampled DNA from nearly every fledged sparrow caught on Lundy, which we then genotyped at 13 polymorphic microsatellite loci (Schroeder et al 2011a;Hsu et al 2015). The usefulness of these loci for parentage analysis is documented elsewhere (Dawson et al 2012).…”
Section: Extrapair Paternitymentioning
confidence: 99%
See 3 more Smart Citations